Unconventional Pathways of Protein Secretion: Mammals vs. Plants - Maricchiolo, Elisa; Panfili, Eleonora; Pompa, Andrea; De Marchis, Francesca; Bellucci, Michele; Pallotta, Maria Teresa (Frontiers in Cell and Developmental Biology, 2022)
In eukaryotes many proteins contain an N-terminal signal peptide that allows their translocation into the endoplasmic reticulum followed by secretion outside the cell according to the classical secretory system. However, an increasing number of secreted proteins lacking the signal peptide sequence is emerging. These proteins, secreted in several alternative ways together known as unconventional protein secretion (UPS) pathways, exert extracellular functions including cell signaling, immune modulation, as well as moonlighting activities different from their well-described intracellular functions. Pathways for UPS include direct transfer across the plasma membrane, secretion from endosomal/multivesicular body-related components, release within plasma membrane-derived microvesicles, or use of elements of autophagy. In this review we describe the mammals and plants UPS pathways identified so far highlighting commonalities and differences.